Design e patrimônio edificado: memórias da arquitetura art déco em Santa Maria resignificadas no mundo da joia - Vargas, Simone Lehnhart (2012)
This study integrates the fields of Design and Cultural Heritage in order to communicate meanings and values of tangible and intangible. It set the following objectives: to identify, select and document, through iconographic material, examples of Art Deco architecture in the Historic Centre of Santa Maria, Rio Grande do Sul, using the architectural framework selected as the inspiration for the design and production of a jewelry collection, final product of this research; contribute to a new way to looking at Santa Maria architectural heritage, especially the Art Deco, as memory, identity and narrative culture and history of the city. The research was didactically structured in three chapters. Chapter I - Literature Review, contextualized study exploring the following themes: Culture, Cultural Heritage, City of Santa Maria, Art History, Product Design, and Semiotics. Chapter II - Methodology, describes the steps undertaken, presented the data obtained from field research and iconographic documentation. Chapter III - Dissertation Results & Discussion, introduced the final product from the research whereas analysis and discussion of the results. Considering the objectives outlined, it was observed they were achieved as the final product contains the characteristics of this research to which it has initially purposed. The jewelry collection "Art Deco Memory" in essence brings a strong and well defined concept, which refers to the bias Deco architecture, providing high added value to the product, mainly because of the theoretical sources that supported the construction of thought and the process of creation. Reframe this heritage in the world figured jewel as a way of evaluating and disseminating the cultural heritage of a particular time and space, providing opportunities for the community to identify its roots and memories, and, as appropriate, construct and reconstruct their values and history.